THE COMPANY'S FINANCIAL PERFORMANCE AS MEASURED USING LIQUIDITY AND PROFITABILITY ANALYSIS IN RETAIL TRADING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) - Muhammad Adi Purwanto; Seflidiana Roza; Nurhayati (Antis Publisher, 2025)
Objective: This study aims to analyze the financial ratios of Liquidity and Profitability to measure financial performance in Retail Trading Companies listed with a sample of 24 Retail Trading sub-sector companies listed on the Indonesia Stock Exchange (IDX) with the Purposive Sampling method for the period 2020-2023. Method: With a sample of 24 Retail Trading sub-sector companies listed on the Indonesia Stock Exchange (IDX) with the Purposive Sampling method for the period 2020-2023. Results: Based on the results of the analysis obtained on financial statements through liquidity ratios known to use Current Ratio known to show an average of 2.399 times, Quick Ratio known to show an average of 1.594 times, and Cash Ratio known to show an average of 0.626 times. So it can be concluded that the company is considered good because the ratio value is above the industry standard of financial ratios and in a liquid state which means that the company is able to fulfill its financial obligations. Meanwhile, the profitability ratio using Return On Asset (ROA) is known to show an average of -38.18%, Return On Equity (ROE) is known to show an average of 19.87%, and Net Profit Margin (NPM) is known to show an average of -4.973%. So it can be concluded that the company is rated Below Average because the ratio value is below the industry standard of financial ratios and has not been able to maintain the level of profit and even the percentage of profit is still in a minus state and has not been able to maximize the company's performance in generating productive profits. Novelty: This study aims to analyze the financial ratios of Liquidity and Profitability to measure financial performance in Retail Trading Companies listed with a sample of 24 Retail Trading sub-sector companies listed on the Indonesia Stock Exchange (IDX) with the Purposive Sampling method for the period 2020-2023.Objective: This study aims to analyze the financial ratios of Liquidity and Profitability to measure financial performance in Retail Trading Companies listed with a sample of 24 Retail Trading sub-sector companies listed on the Indonesia Stock Exchange (IDX) with the Purposive Sampling method for the period 2020-2023. Method: With a sample of 24 Retail Trading sub-sector companies listed on the Indonesia Stock Exchange (IDX) with the Purposive Sampling method for the period 2020-2023. Results: Based on the results of the analysis obtained on financial statements through liquidity ratios known to use Current Ratio known to show an average of 2.399 times, Quick Ratio known to show an average of 1.594 times, and Cash Ratio known to show an average of 0.626 times. So it can be concluded that the company is considered good because the ratio value is above the industry standard of financial ratios and in a liquid state which means that the company is able to fulfill its financial obligations. Meanwhile, the profitability ratio using Return On Asset (ROA) is known to show an average of -38.18%, Return On Equity (ROE) is known to show an average of 19.87%, and Net Profit Margin (NPM) is known to show an average of -4.973%. So it can be concluded that the company is rated Below Average because the ratio value is below the industry standard of financial ratios and has not been able to maintain the level of profit and even the percentage of profit is still in a minus state and has not been able to maximize the company's performance in generating productive profits. Novelty: This study aims to analyze the financial ratios of Liquidity and Profitability to measure financial performance in Retail Trading Companies listed with a sample of 24 Retail Trading sub-sector companies listed on the Indonesia Stock Exchange (IDX) with the Purposive Sampling method for the period 2020-2023.